Analysis of the Utilization of Interactive Flat Panel (IFP) Technology in Enhancing the Quality of Integrated Science and Social Studies (IPAS) Learning in Elementary Schools - Imlasiah Zahro (Asian Journal of Applied Education (AJAE), 2026)
The rapid development of digital technology has encouraged elementary schools to integrate innovative learning media to improve the quality of Integrated Science and Social Studies (IPAS) instruction. One of the technologies adopted is the Interactive Flat Panel (IFP), which creates a more visual, interactive, and participatory learning environment. This study aims to analyze the utilization of Interactive Flat Panels in enhancing the quality of IPAS learning at SD Negeri Petukangan Utara 02. The research is grounded in constructivist theory and employs a qualitative case study approach. Data were collected through observations, interviews, and documentation, while data analysis followed the stages of data reduction, data display, and conclusion drawing. The findings indicate that the use of Interactive Flat Panels enhances classroom interactivity, students' learning motivation, and conceptual understanding. A notable finding of this study is that Interactive Flat Panels function not only as instructional media for content delivery but also as collaborative learning tools that encourage students to participate more actively, express their opinions confidently, and engage in meaningful discussions during IPAS learning.